CHARACTERISTICS OF STYLISTIC EXAMINATION IN THE PEDAGOGICAL INSTRUCTION CONCERNING GRAMMATICAL CONSTRUCTIONS OF THE VERB (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
Stylistic analysis holds considerable importance in educational pedagogy, specifically concerning the intricate structures of verb grammar. This article investigates the attributes of stylistic scrutiny within educational settings, investigating its impact on improving language acquisition results. By conducting an exhaustive literature review and empirical investigation, this study clarifies the diverse methodologies utilized in stylistic analysis, offering compelling perspectives on its educational ramifications.